Climate change adaptation strategies for small-scale Hilsa fishers in the coastal area of Bangladesh: social, economic, and ecological perspectives - Mozumder, Mohammad Mojibul Hoque; Schneider, Petra; Islam, Mohammad Mahmudul; Deb, Dibash; Hasan, Mehedi; Monzer, Md. Abdulla; Nur, As-Ad Ujjaman (Frontiers in Marine Science, 2023)
This study examines social, economic, and ecological adaptation strategies for small-scale Hilsa fishers in Bangladesh’s coastal areas in response to the impacts of climate change. The Hilsa fishery and the communities dependent on it are vulnerable to the adverse effects of climate change, making it imperative to adopt mechanisms to cope with its consequences. Using a mixed-method approach, including in-depth interviews, focus group discussions, and a review of secondary resources, this study explores adaptation policies, relevant factors, and aspects of the Hilsa fishing community’s response to climate change. The study finds that climate change poses a significant threat to biodiversity, potentially leading to changes in fish migration systems and declining fish stocks. The Hilsa fishers perceive that addressing climate change requires policies that combat poverty, preserve or restore biodiversity, and enhance ecosystem services simultaneously. The study identifies social adaptation strategies such as risk reduction, social relationships, and participation in adaptation planning. Economic adaptation strategies include alternative livelihood development, aquaculture, and access to credit. The study also suggests that effective ecological adaptation actions include developing climate change knowledge and fishers’ local ecological knowledge, establishing more effective sanctuaries, and developing networks among protected areas. The study concludes that formal adaptation policies should consider fishers’ interests and practices for adaptation, including their knowledge of social, economic, and ecological issues, to address the impacts of climate change on small-scale fishers and their communities.